Pour un féminisme critique - Braidotti, Rosi (Les Cahiers du GRIF, 1983)
Keywords: 1900-1999; 1980-1989; cours; cycles supérieurs; discipline; fem9000; philosophie; périodes historiques; ressource en ligne; sciences humaines

La même et les différences - Collin, Françoise (Les Cahiers du GRIF, 1983)
Keywords: cours; cycles supérieurs; discipline; fem9000; philosophie; ressource en ligne; sciences humaines; thématiques; écriture des femmes*

« Oppression, » dans The politics of reality, - Frye, Marilyn (The politics of reality: essays in feminist theory, 1983)
Politics of Reality includes nine essays that examine sexism, the exploitation of women, the gay rights movement and other topics from a feminist perspective. The essays "The Problem That Has No Name" and "A Note On Anger" have been translated into Spanish by Maria Lugones for circulation in la Asociacion Argentina de Mujeres en Filosofia.
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; identités LGBTQIA2+; intersectionnalité; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis